FAMILY SUPPORT SYSTEM AND THE BODY IMAGE OF BREAST CANCER PATIENTS UNDERGOING CHEMOTHERAPY IN JAKARTA - Wijayanti, Sekar; Ladesvita, Fiora (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2023)
Background: Cancer and its treatment can trigger pressure on breast cancer patients which can cause health problems both physically, psychologically, physiologically and socially in breast cancer patients. The purpose of this study was to analyze the relationship between family support and body image of breast cancer patients undergoing chemotherapy. Method: The methode in this quantitative research is using a cross sectional design. The sampling technique used was accidental sampling with a total sample of 33 people. Results: the average age of the respondents was 49 years with the majority being female (97%), the last education was high school (66.7%) and the majority were housewives (63.6%), the most common cancer stage was stage II (48, 5%) with an average length of chemotherapy 4 and 5 cycles (27.3%). A total of 19 (57.6%) had good family support and 14 (42.4%) had poor family support. As many as 21 (63.6%) had body image disturbances and 12 (36.4%) did not experience body image disturbances. Conclusion: It can be concluded that there is a significant relationship between family support and body image of breast cancer patients undergoing chemotherapy using the chi-square correlation test with a p-value of 0.003 (<0.05) and OR = 5.6.Recommendation: Increasing family support for breast cancer patients who experience body image problems should be a concern among nurses. Further studies are required by taking into account other risk factors that have a significant impact on body image of breast cancer patients.